The effects of flavanone-rich citrus juice on cognitive function and cerebral blood flow: an acute, randomised, placebo-controlled cross-over trial in healthy, young adults. Issue 12 (16th January 2017) - Lamport, Daniel J.; Pal, Deepa; Macready, Anna L.; Barbosa-Boucas, Sofia; Fletcher, John M.; Williams, Claire M.; Spencer, Jeremy P. E.; Butler, Laurie T.
Abstract: A plausible mechanism underlying flavonoid-associated cognitive effects is increased cerebral blood flow (CBF). However, behavioural and CBF effects following flavanone-rich juice consumption have not been explored. The aim of this study was to investigate whether consumption of flavanone-rich juice is associated with acute cognitive benefits and increased regional CBF in healthy, young adults. An acute, single-blind, randomised, cross-over design was applied with two 500-ml drink conditions – high-flavanone (HF; 70·5 mg) drink and an energy-, and vitamin C- matched, zero-flavanone control. A total of twenty-four healthy young adults aged 18–30 years underwent cognitive testing at baseline and 2-h after drink consumption. A further sixteen, healthy, young adults were recruited for functional MRI assessment, whereby CBF was measured with arterial spin labelling during conscious resting state at baseline as well as 2 and 5 h after drink consumption. The HF drink was associated with significantly increased regional perfusion in the inferior and middle right frontal gyrus at 2 h relative to baseline and the control drink. In addition, the HF drink was associated with significantly improved performance on the Digit Symbol Substitution Test at 2 h relative to baseline and the control drink, but no effects were observed on any other behavioural cognitive tests. These results demonstrate that consumption of flavanone-rich citrus juice in quantities commonly consumed can acutely enhance blood flow to the brain in healthy, young adults. However, further studies are required to establish a direct causal link between increased CBF and enhanced behavioural outcomes following citrus juice ingestion.